The Role Of Direct Marketing In Improving Customer Satisfaction (Field Study At Tishreen University) - قاسم , سامر; السكري, أحمد; دبس, يامن (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to determine the role of direct marketing through its means (direct mail, internet, catalog, phone) in improving customer satisfaction at Tishreen University in Lattakia Governorate. The researcher followed the descriptive and analytical approach in his study, and a set of methods, including relying on secondary and primary data through a questionnaire that was completed It was designed, and it was distributed to (179) respondents, of which (175) were retrieved, and (171) questionnaires were valid for analysis, and the research community was formed from clients of Tishreen University in Lattakia Governorate. The study concluded that there is a statistically significant relationship between Tools of direct marketing (direct mail, internet, catalog, phone) and customer satisfaction. The average of the responses of the sample members for the direct mail variable was 2.41, which indicates that the university does not send its service offers to clients via direct mail, and that the university does not send its offers to current clients only, and that the university does not formulate mail messages (marketing offers) in a personal capacity, and that the rates The response is not very high due to the use of direct mail.